1992
DOI: 10.1177/019459989210600307
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and Topical Surgical Preparation Solution in Septal Surgery

Abstract: One thousand forty patients undergoing septal surgery of the nose were included in this 5-year study of no prophylactic antibiotics and no topical surgical preparation solution before surgery. Minor nasal infections developed in only five patients (0.48%) postoperatively. All five of these patients responded to oral antibiotic therapy and did not require hospitalization or intravenous antibiotic treatment. The incidence of infectious complications resulting from nasal surgery without the use of topical surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 11 publications
1
57
1
Order By: Relevance
“…Yoder and Weimer reported only 5 postoperative infections (0.48%) in 1040 patients undergoing either septoplasty or septorhinoplasty using an endonasal approach. 6) Makitie et al reported 12 postoperative septal abscesses (12%) in 100 patients undergoing septoplasty under local anesthesia by resecting the septal deformities and by reconstructing the septum. 7) Our study revealed eight PSAs (5.7%) in 141 septal surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Yoder and Weimer reported only 5 postoperative infections (0.48%) in 1040 patients undergoing either septoplasty or septorhinoplasty using an endonasal approach. 6) Makitie et al reported 12 postoperative septal abscesses (12%) in 100 patients undergoing septoplasty under local anesthesia by resecting the septal deformities and by reconstructing the septum. 7) Our study revealed eight PSAs (5.7%) in 141 septal surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibiotics in otorhinolaryngological surgeries is a common practice among most ENT doctors, however there are few studies proving the efficacy and need for this practice, which is considered as unnecessary by some authors [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Many otorhinolaryngologists also use topic formulations of antibiotics after nasal surgeries 4,10 . There is no evidence, however, that this practice reduces the incidence of postoperative infection 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations